2020
DOI: 10.3390/polym12051050
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically-Obtained Polysulfonic-Acids Doped Polyaniline Films—A Comparative Study by Electrochemical, Microgravimetric and XPS Methods

Abstract: Polyaniline (PANI) layers are electrochemically obtained in the presence of four polysulfonic acids with different rigidities of the polymer backbone-iso-(and tere-)poly-(4,4′-(2,2′-disulfonic acid)-diphenylene-iso(tere)-phthalamide (i-PASA and t-PASA), polystyrenesulfonic acid (PSSA) and poly(2-acrylamido-2-methyl-1-propanesulfonic acid) (PAMPSA). Combined microgravimetric (EQCM) and electrochemical measurements are carried out in the course of polymerization and repetitive redox switching. It is found that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
(54 reference statements)
1
9
0
Order By: Relevance
“…Furthermore, accommodation of the polymer structure occurring at the repetitive redox transitions may be related to loss of solvent molecules. Such effects were already observed for PASA- and PSSA-doped polyaniline layers [ 35 ].…”
Section: Resultssupporting
confidence: 56%
“…Furthermore, accommodation of the polymer structure occurring at the repetitive redox transitions may be related to loss of solvent molecules. Such effects were already observed for PASA- and PSSA-doped polyaniline layers [ 35 ].…”
Section: Resultssupporting
confidence: 56%
“…One of the ways to increase the chemical and electrochemical stability of PANI is to dope it using large molecule polyacids, instead of small molecule anion dopants [ 1 , 13 , 14 , 15 ]. The Loo Group reported that electroactivity and electrochemical stability can be enhanced by doping PANI using a strong polyacid, poly(2-acrylamide-2-methyl-1-propane sulfonic acid (PAAMPSA)), showing that PANI can reversibly change its oxidation state in neutral and alkaline aqueous solutions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that PANI doped with inorganic ions loses its conductivity for pH > 3 due to decrease of the number of protonated amine species. This drawback was overcome by two different strategies-so-called self-doping (i.e., chemical modification of the main polymer chain to obtain covalently bound acid moieties such as sulfonates or phosphonates) [6][7][8][9][10][11][12][13][14][15][16] and doping by monoorganic acid or poly(organic acid) anions that become steadily immobilized in the PANI structure [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Overlapping double peaks were still distinct in the reductive wave [31]. In the recent years, a series of papers [23,[26][27][28][32][33][34] was devoted to the properties of PANI obtained in the presence of two poly(amidosulfonic acids) that are identical in their chemical composition but differ in the rigidity of their backbone-poly-(4,4′-(2,2′-disulfonic acid)-diphenylene-tere-phthalamide) (t-PASA, rigid backbone) and poly-(4,4′-(2,2′-disulfonic acid)-diphenyleneiso-phthalamide) (i-PASA, semi-rigid backbone). It was shown [26] that PANI/PASA-doped layers retain some extent of electroactivity up to pH 5 but the initial charge is partially lost after treatment in the slightly acidic solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation